Answer

Verified

432.9k+ views

Hint: So we have to integrate$\int{\dfrac{{{x}^{2}}+5x+2}{x+2}}$. Then for that substitute$x+2=t$and then simplify it. Use the sum rule and integrate it. You will get the answer.

Complete step-by-step answer:

So we have to integrate$\int{\dfrac{{{x}^{2}}+5x+2}{x+2}}dx$.

Integration is the reverse of differentiation.

However:

If $y=2x+3,\dfrac{dy}{dx}=2$

If $y=2x+5,\dfrac{dy}{dx}=2$

If $y=2x,\dfrac{dy}{dx}=2$

So the integral of $2$ can be$2x+3,2x+5,2x$etc.

For this reason, when we integrate, we have to add a constant. So the integral of$2$ is$2x+c$, where $c$ is a constant.

An "S" shaped symbol is used to mean the integral of, and$dx$is written at the end of the terms to be integrated, meaning "with respect to $x$". This is the same "$dx$" that appears in$\dfrac{dy}{dx}$.

We have to use the substitution method.

There are occasions when it is possible to perform an apparently difficult piece of integration by first making a substitution. This has the effect of changing the variable and the integrand.

So now let us take an example such that$\int{{{(x+1)}^{4}}}dx$,

So for the above, we know we have solved many integrations like$\int{{{u}^{4}}du}$.

So we can see that instead of$x+1$there is$u$.

So$x+1=u$, differentiating we get $dx=du$. So, our integral becomes :

$\int{{{(x+1)}^{4}}}dx=\int{{{u}^{4}}du}=\dfrac{{{u}^{5}}}{5}+c$

So substituting we get,

$=\dfrac{{{(x+1)}^{5}}}{5}+c$

So like this we have to substitute for this sum as well.

So we have to integrate the above integral$\int{\dfrac{{{x}^{2}}+5x+2}{x+2}}dx$.

So now substituting$x+2=t$.

So differentiating we get,

$dx=du$

And $x=t-2$,

So substituting above we get,

$\int{\dfrac{{{x}^{2}}+5x+2}{x+2}}dx=\int{\dfrac{{{(t-2)}^{2}}+5(t-2)+2}{t}}du$

So simplifying we get,

$=\int{\dfrac{{{(t-2)}^{2}}+5(t-2)+2}{t}}du=\int{\dfrac{{{t}^{2}}-4t+4+5t-10+2}{t}}du=\int{\dfrac{{{t}^{2}}+t-4}{t}}du$

So now splitting the terms we get,

$=\left( \int{\dfrac{{{t}^{2}}}{t}+\dfrac{t}{t}}-\dfrac{4}{t} \right)dt$

Next, we’ll simplify and apply the sum rule.

Sum rule is$\int{(a+b)}dx=\int{adx+}\int{bdx}$.

So, applying it and simplifying further, we get,

$=\left( \int{\dfrac{{{t}^{2}}}{t}+\dfrac{t}{t}}-\dfrac{4}{t} \right)dt=\int{tdt+\int{dt-\int{\dfrac{4}{t}dt}}}$

Now, let’s try applying integration.

We know, that$\int{{{p}^{n}}dp=\dfrac{{{p}^{n+1}}}{n+1}}+c$and$\int{\dfrac{1}{p}dp=\log p+c}$

So applying these properties, we get,

$=\dfrac{{{t}^{2}}}{2}+t-4\log t+c$

So now substituting the value, we get,

$=\dfrac{{{(x+2)}^{2}}}{2}+(x+2)-4\log (x+2)+c$

So we get the final answer $\int{\dfrac{{{x}^{2}}+5x+2}{x+2}}=\dfrac{{{(x+2)}^{2}}}{2}+(x+2)-4\log (x+2)+c$

Note: You should know the basic things of integration. So here substitution is important. It depends on you what you are substituting. You should know$\int{{{p}^{n}}dp=\dfrac{{{p}^{n+1}}}{n+1}}+c$and$\int{{{p}^{n}}dp=\dfrac{{{p}^{n+1}}}{n+1}}+c$. Also, you must know the rules of integration. Avoid silly mistakes because silly mistakes change the whole problem.

Complete step-by-step answer:

So we have to integrate$\int{\dfrac{{{x}^{2}}+5x+2}{x+2}}dx$.

Integration is the reverse of differentiation.

However:

If $y=2x+3,\dfrac{dy}{dx}=2$

If $y=2x+5,\dfrac{dy}{dx}=2$

If $y=2x,\dfrac{dy}{dx}=2$

So the integral of $2$ can be$2x+3,2x+5,2x$etc.

For this reason, when we integrate, we have to add a constant. So the integral of$2$ is$2x+c$, where $c$ is a constant.

An "S" shaped symbol is used to mean the integral of, and$dx$is written at the end of the terms to be integrated, meaning "with respect to $x$". This is the same "$dx$" that appears in$\dfrac{dy}{dx}$.

We have to use the substitution method.

There are occasions when it is possible to perform an apparently difficult piece of integration by first making a substitution. This has the effect of changing the variable and the integrand.

So now let us take an example such that$\int{{{(x+1)}^{4}}}dx$,

So for the above, we know we have solved many integrations like$\int{{{u}^{4}}du}$.

So we can see that instead of$x+1$there is$u$.

So$x+1=u$, differentiating we get $dx=du$. So, our integral becomes :

$\int{{{(x+1)}^{4}}}dx=\int{{{u}^{4}}du}=\dfrac{{{u}^{5}}}{5}+c$

So substituting we get,

$=\dfrac{{{(x+1)}^{5}}}{5}+c$

So like this we have to substitute for this sum as well.

So we have to integrate the above integral$\int{\dfrac{{{x}^{2}}+5x+2}{x+2}}dx$.

So now substituting$x+2=t$.

So differentiating we get,

$dx=du$

And $x=t-2$,

So substituting above we get,

$\int{\dfrac{{{x}^{2}}+5x+2}{x+2}}dx=\int{\dfrac{{{(t-2)}^{2}}+5(t-2)+2}{t}}du$

So simplifying we get,

$=\int{\dfrac{{{(t-2)}^{2}}+5(t-2)+2}{t}}du=\int{\dfrac{{{t}^{2}}-4t+4+5t-10+2}{t}}du=\int{\dfrac{{{t}^{2}}+t-4}{t}}du$

So now splitting the terms we get,

$=\left( \int{\dfrac{{{t}^{2}}}{t}+\dfrac{t}{t}}-\dfrac{4}{t} \right)dt$

Next, we’ll simplify and apply the sum rule.

Sum rule is$\int{(a+b)}dx=\int{adx+}\int{bdx}$.

So, applying it and simplifying further, we get,

$=\left( \int{\dfrac{{{t}^{2}}}{t}+\dfrac{t}{t}}-\dfrac{4}{t} \right)dt=\int{tdt+\int{dt-\int{\dfrac{4}{t}dt}}}$

Now, let’s try applying integration.

We know, that$\int{{{p}^{n}}dp=\dfrac{{{p}^{n+1}}}{n+1}}+c$and$\int{\dfrac{1}{p}dp=\log p+c}$

So applying these properties, we get,

$=\dfrac{{{t}^{2}}}{2}+t-4\log t+c$

So now substituting the value, we get,

$=\dfrac{{{(x+2)}^{2}}}{2}+(x+2)-4\log (x+2)+c$

So we get the final answer $\int{\dfrac{{{x}^{2}}+5x+2}{x+2}}=\dfrac{{{(x+2)}^{2}}}{2}+(x+2)-4\log (x+2)+c$

Note: You should know the basic things of integration. So here substitution is important. It depends on you what you are substituting. You should know$\int{{{p}^{n}}dp=\dfrac{{{p}^{n+1}}}{n+1}}+c$and$\int{{{p}^{n}}dp=\dfrac{{{p}^{n+1}}}{n+1}}+c$. Also, you must know the rules of integration. Avoid silly mistakes because silly mistakes change the whole problem.

Recently Updated Pages

Three beakers labelled as A B and C each containing 25 mL of water were taken A small amount of NaOH anhydrous CuSO4 and NaCl were added to the beakers A B and C respectively It was observed that there was an increase in the temperature of the solutions contained in beakers A and B whereas in case of beaker C the temperature of the solution falls Which one of the following statements isarecorrect i In beakers A and B exothermic process has occurred ii In beakers A and B endothermic process has occurred iii In beaker C exothermic process has occurred iv In beaker C endothermic process has occurred

The branch of science which deals with nature and natural class 10 physics CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Define absolute refractive index of a medium

Find out what do the algal bloom and redtides sign class 10 biology CBSE

Prove that the function fleft x right xn is continuous class 12 maths CBSE

Trending doubts

Difference Between Plant Cell and Animal Cell

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Write two gases which are soluble in water class 11 chemistry CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Fill the blanks with proper collective nouns 1 A of class 10 english CBSE

What organs are located on the left side of your body class 11 biology CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths